2017
DOI: 10.1038/srep46129
|View full text |Cite
|
Sign up to set email alerts
|

Linoleic acid isomerase gene FgLAI12 affects sensitivity to salicylic acid, mycelial growth and virulence of Fusarium graminearum

Abstract: Fusarium graminearum is the major causal agent of fusarium head blight in wheat, a serious disease worldwide. Linoleic acid isomerase (LAI) catalyses the transformation of linoleic acid (LA) to conjugated linoleic acid (CLA), which is beneficial for human health. We characterised a cis-12 LAI gene of F. graminearum (FGSG_02668; FgLAI12), which was downregulated by salicylic acid (SA), a plant defence hormone. Disruption of FgLAI12 in F. graminearum resulted in decreased accumulation of cis-9,trans-11 CLA, enha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 47 publications
0
14
0
Order By: Relevance
“…HAM medium has linoleic acid, lipoic acid, thymidine, cupric sulfate, and zinc sulfate as differentiated constituents from other media. Among these constituents, linoleic and lipoic acids are important for the energy metabolism of cells ( Casu et al, 2016 , 2018 ; Zhang et al, 2017 ). Thymidine is important in cell multiplication ( Shields et al, 1998 ).…”
Section: Discussionmentioning
confidence: 99%
“…HAM medium has linoleic acid, lipoic acid, thymidine, cupric sulfate, and zinc sulfate as differentiated constituents from other media. Among these constituents, linoleic and lipoic acids are important for the energy metabolism of cells ( Casu et al, 2016 , 2018 ; Zhang et al, 2017 ). Thymidine is important in cell multiplication ( Shields et al, 1998 ).…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, in barley, ICS overexpression increases the SA concentration, while also repressing F. graminearum infections at 24 and 48 hpi but not at later infection stages [ 10 ]. Additionally, SA adversely affects the cell wall and cell membrane of F. graminearum by downregulating the expression levels of the fungal class VIII chitin synthase gene ( FgCHS8 ) and the cis -12 linoleic acid isomerase gene ( FgLAI12 ) [ 23 , 24 ], which may inhibit conidial germination and mycelial growth [ 16 ]. However, the application of exogenous SA to wheat heads reportedly does not enhance wheat FHB resistance, even at very high concentrations [ 16 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, previous studies revealed that the infection of wheat heads by F. graminearum stimulates the considerable accumulation of SA and the expression of SA-related genes [ 21 , 22 ]. Moreover, SA significantly and directly affects F. graminearum by inhibiting mycotoxin production, conidial germination and mycelial growth [ 16 ] by downregulating the expression of the chitin synthase gene FgCHS8 and the cis -12 linoleic acid isomerase gene FgLAI12 [ 23 , 24 ]. Deletion of the SA exporter gene FgABCC9 results in increased sensitivity to SA, decreased accumulation of the mycotoxin deoxynivalenol (DON) and fewer blight symptoms in wheat [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, we observed that F. graminearum is able to strengthen the outer cell wall by upregulating the expression of FgCWM1 (Figure 3b) under SA stress. This is despite the SA-induced downregulation of FgLAI12 (linoleic acid isomerase gene) and FgCHS8 in F. graminearum , which encode important components of the fungal cell membrane and cell wall, respectively, and are essential for the fungal response to SA [28,29]. Compared with spikes inoculated with the WT strain, those inoculated with Δ FgCWM1 accumulated more SA (Figure 6f), confirming the key role of FgCWM1 in the fungal response to wheat endogenous SA.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, SA treatments have been shown to decrease the germination efficiency and mycelial growth of F. graminearum and decrease DON production [22]. In our previous study, we found that SA downregulated the expression of FgLAI12 (linoleic acid isomerase gene) and FgCHS8 (chitin synthase gene) in F. graminearum ; these genes encode components of the fungal cell membrane and cell wall, respectively, and are essential for the fungal response to stress conditions, including SA [28,29]. However, F. graminearum can efficiently export and metabolize SA [23,24,30] to reduce its toxicity.…”
Section: Introductionmentioning
confidence: 99%